Assessment of frailty and related outcomes in older patients with heart failure: A cohort study - Georgios Tournas; Christos Kourek; Vassiliki Mantzaraki; Georgios Georgiopoulos; Constantinos Pantos; Savvas Toumanidis; Alexandros Briasoulis; Ioannis Paraskevaidis (Hellenic Journal of Cardiology, 2022)
Objective: Heart failure (HF) is a common cause of morbidity and mortality in older patients. Frailty is prevalent and complicates the course of HF. We sought to investigate the impact of frailty on HF outcomes. Methods: Patients over 65 years old hospitalized with acute decompensated HF and mildly reduced or preserved EF, between September 2017 and September 2019 were enrolled in the study. Before hospital discharge at euvolemic state, patients underwent six-minute walk test (6MWT) and frailty assessment using FRIED and modified SOF scores. Predictors of death, readmissions, and increase in diuretic dose were analyzed by multivariable logistic regression models. Results: We enrolled 193 consecutive patients (mean age 78.6 ± 8.4 years, 29.5% males, 59.6% with HF and preserved EF). All patients had at least one comorbidity (40.9% coronary artery disease, 71% diabetes, and 86% hypertension). The mean 6MWT distance was 316.2 meters. According to FRIED score, 4.7% were normal and 17.6% were categorized as pre-frail and 77.7% as frail, while according to SOF index 9.8% were normal, 15% were categorized as pre-frail and 75.1% as frail. Frail patients according to both indices had a higher risk of 90-day readmissions, uptitration of diuretics within 90 days (p < 0.001 for both) and numerically but not significantly higher risk of death. Frailty status was independently associated with higher risk of 90-day readmissions, uptitration of diuretics, and higher BNP at 90 days. Conclusions: Frailty in older patients with HF is common and associated with worse prognosis. Pre-discharge frailty assessment may aid in identification of patients at high-risk for short-term complications.